Differentiating Fetal Alcohol Spectrum Disorder from other neurodevelopmental disorders: neurocognitive and socio-emotional evidence - Fernandes-Magalhaes, Roberto; Labrado, Lorena; Ferrera, David; Fernández-Sánchez, Marisa; del Pino, Ana Belén; Soldic, Dino; Pazos-García, Sarai; De Lahoz, María Eugenia; Peláez, Irene; Barjola, Paloma; Mercado, Francisco (Frontiers in Neuroscience, 2025)
BackgroundFetal Alcohol Spectrum Disorder (FASD) is associated with widespread cognitive, behavioral, and adaptive impairments. Its clinical presentation often overlaps with other neurodevelopmental conditions (ND), such as learning disorders (LD) or Attention-Deficit/Hyperactivity Disorder (ADHD), making differential diagnosis challenging. Although syndrome-specific cognitive patterns have been suggested, a distinctive neurocognitive profile of FASD remains inconclusive.MethodSeventy-six children (46 with FASD and 30 with ND), aged 6–15 years (M = 11.00, SD = 2.30), completed a comprehensive neuropsychological battery, covering domains of intellectual functioning, attention, memory, verbal skills, executive functions, and socio-emotional behavior.ResultsAs compared to normative ranges, children with FASD felt below expected levels in cognitive functioning. Moreover, children with FASD showed significantly lower performance than those with ND across all cognitive domains, including global intelligence, verbal comprehension, working memory, processing speed, attention, memory, and executive functions. At the socio-emotional level, parental reports revealed that children with FASD scored higher than their peers with ND on anxiety, social and thought problems, attentional difficulties, and aggression behavior, although most of them remained within non-clinical ranges.ConclusionFindings support the presence of a distinctive neurocognitive profile in FASD characterized by generalized cognitive deficits and domain-specific impairments (particularly in attention, memory, and executive functions). In addition, children with FASD scored higher on socio-emotional difficulties, although still within non-clinical ranges. These results highlight the clinical relevance of domain-specific assessment and underscore the need for early diagnosis and targeted evidence-based interventions to mitigate long-term cognitive and adaptive challenges associated with prenatal alcohol exposure.